Correlation between level of serum estrogen, c-telopeptide, and interleukin-6 in determining bone density in perimenopausal women - Suparman, Eddy (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To evaluate the role of estrogen as a menopausal biochemical marker to c-telopeptide (CTx) and IL-6 as a biochemical marker of mineral bone density in perimenopausal women. Method: This is an observational, cross-sectional study in perimenopausal women between 45 - 51 years old, who matched the inclusion and exclusion criteria such as no contraception was taken before, no specific disease that could affect the laboratory findings. Samples were taken from outpatients clinic of Prof Dr. R.D. Kandou hospital. The patients were gathered for blood samples collection. Blood samples were tested in laboratory. All data were collected and being processed statistically using Pearson correlation coefficient (SPSS version 16). Result: From 60 perimenopausal women (45 - 51 years old) sample, mean age was 47.98 ± 2.26 SD. Estrogen (estradiol) level: < 10 pg/ml, maximum 358 pg/ml, and mean 77.11 ± 86.2 SD. IL-6 level: minimum is 1.645 pg/ml, maximum 7.771 pg/ml, and mean 4.317 ± 2.112 SD. We found significant correlation between age and estrogen level (correlation level < 0.05) and CTx level (in level < 0.01). From regression curve, age has no significant correlation with IL-6 concentration. However, we found significant correlation between estradiol and CTx and IL-6 with respective correlation coefficient value of < 0.01. Likewise the correlation between CTx and IL- 6 showed significant statistically with the value of the correlation coefficient < 0,01. Conclusion: There is a significant correlation between estrogen, Il-6 and CTx. These variables play an important role in the occurrence of the physiological changes in the perimenopausal women. This study also showed the occurrence of a bone reabsorption process that was marked by the increase of CTx level in accordance with the increase in the age and the increase in the level of CTx together with the decline in the level of oestrogen. Therefore, prevention therapy of osteoporosis should begin in earlier age, before the further bone reabsorption take place. [Indones J Obstet Gynecol 2010; 34-2: 84-8] Keywords: c-telopeptide, bone mineral density, estrogen, interleukin- 6, perimenopause women